Unmet Support Service Needs and Health-Related Quality of Life among Adolescents and Young Adults with Cancer: The AYA HOPE Study - Smith, Ashley W.; Parsons, Helen M.; Kent, Erin E.; Bellizzi, Keith M.; Zebrack, Brad J.; Keel, Gretchen; Lynch, Charles; Rubenstein, Mara B.; Keegan, Theresa H. (Frontiers in Oncology, 2013)
Introduction: Cancer for adolescents and young adults (AYA) differs from younger and older patients; AYA face medical challenges while navigating social and developmental transitions. Research suggests that these patients are under- or inadequately served by current support services, which may affect health-related quality of life (HRQOL). Methods: We examined unmet service needs and HRQOL in the National Cancer Institute’s Adolescent and Young Adult Health Outcomes and Patient Experience (AYA HOPE) study, a population-based cohort (n=484), age 15-39, diagnosed with cancer 6-14 months prior, in 2007-2009. Unmet service needs were psychosocial, physical, spiritual, and financial services where respondents endorsed that they needed, but did not receive, a listed service. Linear regression models tested associations between any or specific unmet service needs and HRQOL, adjusting for demographic, medical and health insurance variables. Results: Over one-third of respondents reported at least one unmet service need. The most common were financial (16%), mental health (15%), and support group (14%) services. Adjusted models showed that having any unmet service need was associated with worse overall HRQOL, fatigue, physical, emotional, social, and school/work functioning, and mental health (p’s<0.0001). Specific unmet services were related to particular outcomes (e.g., needing pain management was associated with worse overall HRQOL, physical and social functioning (p’s<0.001)). Needing mental health services had the strongest associations with worse HRQOL outcomes; needing physical/occupational therapy was most consistently associated with poorer functioning across domains. Discussion: Unmet service needs in AYAs recently diagnosed with cancer are associated with worse HRQOL. Research should examine developmentally appropriate, relevant practices to improve access to services demonstrated to adversely impact HRQOL, particularly physical therapy and mental health services.